An Implementation of a Frequency Decomposition Algorithm for Power Quality Smoothening in a Hybrid SPVA-BES Microgrid - Srivastava, Divyank; Narayanan, Vivek; Singh, Bhim; Verma, Arunima (IEEE transactions on industrial informatics, 2024)
This article presents a novel application of Fourier decomposition method in a double-stage grid-tied microgrid integrating a solar photovoltaic array (SPVA) and battery energy storage (BES). Due to intermittent nature of SPVA generation and the nonlinearity of local loads connected at point of common coupling, the grid is subject to harmonic distortions. The proposed control method decomposes nonlinear and nonstationary signals to extract fundamental components necessary for generating switching pulses for voltage source converter. To ensure reliable operation during grid outages, system incorporates a BES, managed using a bidirectional dc-dc converter. This configuration maintains high-quality power delivery, and facilitates a smooth transition between grid-connected mode and standalone mode. Simulation and hardware prototype results validate effective operation of proposed control strategy.